PENERAPAN AKAD MUSYARAKAH MUTANAQISAH DALAM PEMBIAYAAN KREDIT PEMILIKAN RUMAH PADA BANK MUAMALAT SIDOARJO - NOVITASARI, INDAH (Jurnal Akuntansi AKUNESA, 2014)
Musyarakah mutanaqisah is one type of cooperation agreement between  two parties with the provisions of section one of the funding partners will be gradually transferred to other partners so that the fund will decline and at the end of the contract the other partner will be the full owner of the contract. The purpose of this research to know application of musyarakah mutanaqisah in house financing credit at Muamalat Bank Sidoarjo, both operationally and accounting statement. The methods that used is descriptive qualitative. The results of this research is showing musyarakah mutanaqisah that using by Muamalat Bank Sidoarjo in house financing credit is occurred joint venture between bank and customer, where customer has to pay to the bank with the same portion belonged to the bank. Keywords : house financing, musyarakah, mutanaqisah, Bank Muamalat,